Victorian Verse The Poetics of Everyday Life - Behlman, Lee.; Loksing Moy, Olivia (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"This exhilarating collection opens up crucial glimpses into the widely and even wildly disparate historical and theoretical practices of Victorian poetic studies in our time. With its revelatory showcasing of the forms and forces of "mere verse," this is a volume to relish and debate." -Tricia Lootens, Josiah Meigs Distinguished Teaching Professor of English emerita, University of Georgia "This wonderful volume gives us a new way to comprehend Victorian poetry. Specifically, it expands the field of Victorian poetry studies by reminding us of the period's rich terrain of verse forms... The Introduction clearly and elegantly lays out the issues -- and it is a pleasure to read, as are the individual essays collected here, written by many of the greatest critics of Victorian poetry writing today." -Carolyn Williams, Distinguished Professor of English, Rutgers University "While Victorian Verse addresses major poets, particularly Christina Rossetti, it also shows how verse punctuated factory life, occupied physical space, filled periodicals, and wove into worship....[This book] successfully gives readers a stirring new sense of a heretofore underestimated genre, and anyone who cares about Victorian daily life will find revelatory ideas in this collection." - Talia Schaffer, Professor of English, CUNY Graduate Center & Queens College Victorian Verse: The Poetics of Everyday Life casts new light on nineteenth-century poetry by examining its popular verse forms and their surrounding social and media landscape. The volume offers insight into two central concepts of both the Victorian era and our own-status and taste-and how cultural hierarchies then and now were constructed and broken. By recovering the lost diversity of Victorian verse, this collection maps the breadth of Victorian writing and reading practices, illustrating how seemingly minor verse genres actually performed crucial social functions for Victorians, in education, leisure practices, the cultural production of class, and the formation of individual and communal identities. In addition to exploring lesser-known and even anonymous versifiers, the essays consider how "major" Victorian poets were also committed to writing and reading "minor" verse. Lee Behlman is Associate Professor of English and Honors Program Director at Montclair State University. Olivia Loksing Moy is Associate Professor of English at the City University of New York, Lehman College.
Introduction -- Chapter One: Workplace Verse: Poetry, Performance and the Industrial Worker -- Chapter Two: Sonnet Contests and Poetic Parlor Games -- Chapter Three: Christina Rossetti's Verses -- Chapter Four: Anti-Elitist Elitist Verse Forms: Comic Ballades and Rondeaus in Punch and Fun -- Chapter Five: "Of china that's ancient and blue": Andrew Lang and the Idea of Form" -- Chapter Six: Victorian Verse on the Colonial Frontier: Eliza Hamilton Dunlop and the Versification of Settler Colonial Culture in Australia -- Chapter Seven: William Barnes's Dual Vocation and the Management of Feeling -- Chapter Eight: Decisions and Revisions and Revolutions: History as Verse in Thomas Carlyle -- Chapter Nine: Commemorating the 1834 Parliament Fire in Satirical and Somber Verse -- Chapter Ten: Rossetti in the Nursery: The Speaking Silences of Sing-Song -- Chapter Eleven: Playing Along: The Verse in Victorian Poetry.
Keywords: Literature, Modern -- 19th century; Poetry; Children's literature; Ethnology -- Great Britain; Culture; Nineteenth-Century Literature; Poetry and Poetics; Children's Literature; British Culture